2015
DOI: 10.1590/0103-8478cr20141856
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity of Aspergillus westerdijkiae to females and oothecae of Periplaneta Americana

Abstract: Cockroach control is performed by the application of chemical insecticides which exert high selective pressure on populations and introduces synthetic substances in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…This is the first finding reporting the alterations in different types of haemocytes in S. litura under SEM. The technique has been used to observe and characterize the haemocytes of different insects in various reports [68,69] and also to observe the spores accumulation in the body of the insect after fungal infection [70][71][72][73]. However, similar types of morphological changes as observed in the present finding were demonstrated by other workers due to entomopathogenic fungi and insecticides under light microscopy [74][75][76][77].…”
Section: Discussionsupporting
confidence: 76%
“…This is the first finding reporting the alterations in different types of haemocytes in S. litura under SEM. The technique has been used to observe and characterize the haemocytes of different insects in various reports [68,69] and also to observe the spores accumulation in the body of the insect after fungal infection [70][71][72][73]. However, similar types of morphological changes as observed in the present finding were demonstrated by other workers due to entomopathogenic fungi and insecticides under light microscopy [74][75][76][77].…”
Section: Discussionsupporting
confidence: 76%
“…In this work was additionally found a number of nonpathogenic OTUs, being some of them described in the literature as presenting the useful features of antagonism against phytopathogens, such as Chaetomium globosum (Awad et al, 2014), Epicoccum nigrum (Fávaro et al, 2012), Penicillium brevicompactum (Jackson et al, 1997) and Trichoderma koningii (Reddy et al, 2014), and/or entomopathogenecity (e.g. Aspergillus westerdijkiae; Baggio et al, 2016). There is very limited information on isolation and characterization of epiphytes and endophytes from fresh olives.…”
Section: Discussionmentioning
confidence: 87%
“…Aggarwal, 2015;Biswas et al, 2012;Fávaro et al, 2012;Lahlali and Hijri, 2010); however, this is the first work showing an effective antagonist activity of these two species against C. acutatum. Similarly, studies examining antagonistic effect of A. westerdijkiae against phytopathogens have never been performed, being only tested its entomopathogenic properties against Periplaneta americana (Baggio et al, 2016). The suppression of C. acutatum growth by fungal isolates tested was mediated mostly at distance and/or in its vicinity, and in less extended following contact.…”
Section: Discussionmentioning
confidence: 99%
“…Among the tested Aspergillus species, A. westerdikijae was found to be the fourth most virulent to fruit flies. A study conducted by Baggio et al (2015) [45] reported that A. westerdijkiae was pathogenic to adult females and oothecae of the American cockroach (Periplaneta americana, Blattidae). This fungus is also known to produce ochratoxin A (OTA) as a contaminant in coffee beans in many parts of the world, including Vietnam [46] and Thailand [47].…”
Section: Discussionmentioning
confidence: 99%